Regional Cooperation between Latin America and the European Union: A Strategic Driver for the 2030 Agenda (Comillas Journal of International Relations, 2023)
The current global context, in the midst of recovering from the crises resulting from the COVID-19 pandemic and the war in Ukraine, calls for a rethink of strategies and priorities to achieve national and international goals, in particular those related to the 2030 Agenda goals. The response to this scenario supports the adequacy of multilateral approaches, which seem to be the only ones capable of achieving effective partnerships, underpinned by shared values and interests and a rules-based world order, as opposed to more restricted approaches. As an example of this approach, this paper claims EU-Latin America and the Caribbean cooperation as a fundamental strategic driver to promote the 2030 Agenda without neglecting the programmes of transition — green, digital, energy — in both regions. This driver will only be efficient if the social dimension is taken into account in all cooperation actions.
Keywords: European Union; Mercosur; Latin American and the Caribbean; sustainable development; 2030 Agenda; multilateralism